KONSEP PENDIDIK DALAM SURAH AR-RAHMAN AYAT 1-4 (STUDI TAFSIR TARBAWI) - Nisrina, Prajihan (JURNAL PENDIDIKAN IPS, 2024)
In the context of Islamic education, educators or teachers play a crucial role in the learning process and serve as role models for their students. Educators are not only responsible for delivering educational material but also for guiding students to apply their knowledge in daily life. Therefore, to ensure that all educators can perform their duties effectively, a conceptual framework is needed to provide clarity and direction regarding their roles as educators. This study aims to examine the concept of teachers as outlined in Surah Ar-Rahman, verses 1-4. The research employs a qualitative approach using library research methods, which are then analyzed in-depth to uncover the meaning and implications of the verses on the concept of educators. The findings indicate that there are four essential aspects an educator must possess: a good personality, knowledge, the ability to develop students' potential, and effective delivery of educational material.